(3JfejI egGQGJ JNWjW GdehGQO GdHTQjIs - (3HSjhfj eMeO(B, (3GdHQGOYjs ((3GdbGgQI(B:s (3GjJQGc ddWHGYI hGdfTQ(B,s, 2005)
(3CgejI GdehGQO GdHTQjI, CfTWI GOGQI GdehGQO GdHTQjI, GdOdjd GdYdej dJNWjW GdehGQO GdHTQjI, eKGd JWHjbj Ydi JNWjW GfTWI GdehGQO GdHTQjI WHbG ddJNWjW GdGSJQGJjLj dEMOi GdTQcGJ(B.s
(3GdeQGLY U(B.224s
Keywords: (3EOGQI GdCaQGOs; (3GdehGQO GdHTQjIs